Effectiveness of Video Assisted Teaching Module Regarding Knowledge of Breast Self-Examination among Girls (International Journal of Nursing Education, 2019)
Breast cancer is the most common cause of death among women worldwide. Breast self-exam (BSE) is considered an important public health procedure; primary prevention should be given the highest priority in the fight against cancer. Pre-experimental one group pre-test post-test research design was adopted. The knowledge score of ANM 1st year Students in post-test shows majority i.e., 95.8 percent acquired above average knowledge while, 4.2 percent had average knowledge and none of them had below average knowledge. The calculated value of paired t-test is 25.846 is greater than the tabulated value of paired t-test with 69 degree of freedom i.e.2. It shows that the VATM was effective.